Portrayal of the different types of the Feedback Move (F-Move) in University classrooms - Galegane, Golebamang (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2019)
Portrayal of the different types of the Feedback Move (F-Move) in University classrooms By: Dr Golebamang Galegane University of Botswana Centre for Academic Development Communication and Study Sills E-mails: galegane@mopipi.ub.bw galeganeg@gmail.com Abstract The Feedback Move (F-Move) is an important aspect of classroom interaction. The objective of this study is to find out how the different types of the F-Move contribute to the development of classroom talk. The Mixed Method Approach, consisting of Classroom and Systematic Observations were used to find out the different types of the F-Move which were used at University. These were administered to a convenience sample of seven Communication and Study Skills classes. The figures from the quantitative results indicate that various types of the F-Move were used by the lecturers during the classroom interaction. On the other hand, the outcome from the qualitative results illustrate that there was lecturer dominance of the F-Move during the teaching and learning process. This was shown by the high percentages of the "Accept” and "Comment” types of the foregoing move. The conclusion drawn from this study is that the lecturers take a considerable amount of time summing up the lesson by way of building more on what was said as a form of feedback (lecturer dominance).